Implementasi Pendekatan TaRL pada Materi Perbanyakan Tanaman Secara Generative untuk Meningkatkan Hasil Belajar Peserta Didik - Ningsih, Sri Sulastri; Nurwahyunani, Atip; Maulida, Zanny Varah (Universitas PGRI Semarang, 2025)
educate the younger generation. However, there are still many obstacles, including differences in characteristics and learning needs of students. This research aims to determine the learning method using the TaRL (Teaching at The Right Level) approach in generative plant propagation material on the level of students' understanding. This type of research is classroom action research. The research subjects using 1 class X of SMK Negeri 1 Bawen were 31 students. This research was carried out by providing pre-test and post-test questions regarding generative plant propagation. The implementation of the TaRL approach is carried out by grouping students according to their respective levels of ability, where each group consists of students who get low, medium and high scores. Grouping is done so that cooperation in groups and discussion activities to complete tasks can run smoothly and effectively. The research that has been carried out shows that the TaRL approach can improve students' understanding. The results of the research showed that there was an increase in students' understanding with the increase in the test results by 5.41 or increased from 84.29 to 89.70.